2020
DOI: 10.1590/1980-57642020dn14-010013
|View full text |Cite
|
Sign up to set email alerts
|

Hermann Rorschach: From klecksography to psychiatry

Abstract: Hermann Rorschach was a Swiss psychiatrist and psychoanalyst, best known for developing a projective test known as the Rorschach inkblot test, a test designed to reflect unconscious parts of the personality that project into the visual stimuli generated by the inkblots, allowing a psychodiagnosis to be established. The technique he developed has been applied since 1921 in a number of countries. Although it has long remained controversial and divided opinions, this did not prevent it from overcoming the barrier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Hermann Rorschach claimed that the test could differentiate patients with psychosis from normal controls. 29 Subsequent studies have indicated that the Rorschach test effectively distinguishes psychosis with fair reliability, validity, and diagnostic efficiency. 30 , 31 Additionally, a meta-analysis has previously demonstrated the Rorschach test's utility in evaluating psychosis or formal thought disorder.…”
Section: Methodsmentioning
confidence: 99%
“…Hermann Rorschach claimed that the test could differentiate patients with psychosis from normal controls. 29 Subsequent studies have indicated that the Rorschach test effectively distinguishes psychosis with fair reliability, validity, and diagnostic efficiency. 30 , 31 Additionally, a meta-analysis has previously demonstrated the Rorschach test's utility in evaluating psychosis or formal thought disorder.…”
Section: Methodsmentioning
confidence: 99%